The Siri’ Culture of Makassar Women in Pakarena Anida Dance - Khalik, Suhartini; Mustika, Maryam (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
Makassar ethnic is one of the ethnic in Indonesia, precisely in South Sulawesi. Previously, local values ​​were still deeply embedded in Makassar women, one of which was shame or Siri’ culture. Nowadays, Makassar women have been influenced by modernization behavior and technological trends, which largely affect the value of Siri' on Makassar women. Realizing this, a good principle instilled in Makassar women is to re-introduce the shame or Siri'. The purpose of this study was to determine the Siri' culture in Makassar women which can be used as a guide in life. Pakarena Anida dance contains values ​​that serve as guidelines for Makassar women to determine their attitude in what they should be. The values ​​contained in the Pakarena Anida dance are life values ​​that uphold self-respect, politeness, and patience. The method used is descriptive qualitative with ethnocoreology approach